2001
DOI: 10.1128/aac.45.12.3580-3584.2001
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activities and Postantifungal Effects of the Potent Dolastatin 10 Derivative Auristatin PHE

Abstract: The pentapeptide dolavaline-valine-dolaisoleuine-dolaproine-phenylalanine-methyl ester (auristatin PHE) is a derivative of the anticancer drug dolastatin 10 (dolavaline-valine-dolaisoleuine-dolaproine-dolaphenine). Broth microdilution assays with a wide variety of yeast and filamentous fungal species demonstrated the specificity of auristatin PHE for Cryptococcus neoformans and several species of Trichosporon. The duration of the postantifungal effect (PAFE) for C. neoformans was determined for exposure times … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Several studies have shown that peptides from different sources such as sea hare Turner et al, 1998;Madden et al, 2000;Vaishampayan et al, 2000;Woyke et al, 2001), fish sauce (Thang and Zhao, 2015;Bah et al, 2016), and cod (Xhindoli et al, 2016) were able to block proliferation of carcinogenic cells. However, it seems there is still a long way in order to make commercial use of these potentially potent anticancer peptides to treat different kinds of cancer.…”
Section: Cytomodulatory Effectmentioning
confidence: 99%
“…Several studies have shown that peptides from different sources such as sea hare Turner et al, 1998;Madden et al, 2000;Vaishampayan et al, 2000;Woyke et al, 2001), fish sauce (Thang and Zhao, 2015;Bah et al, 2016), and cod (Xhindoli et al, 2016) were able to block proliferation of carcinogenic cells. However, it seems there is still a long way in order to make commercial use of these potentially potent anticancer peptides to treat different kinds of cancer.…”
Section: Cytomodulatory Effectmentioning
confidence: 99%
“…In the fungus Uromyces appendiculatus, dolastatin 10 disrupts microtubules (41). We recently reported that a 4-h exposure to Ն2.6 M auristatin PHE (4 times the MIC, as determined in RPMI medium) resulted in a C. neoformans population consisting almost entirely (ϳ97%) of large-budded cells (50). These results led us to evaluate the effects of auristatin PHE on the microtubule organization of C. neoformans and to compare them to those of a compound known to interfere with the microtubule cytoskeleton in yeast (17,21).…”
Section: Discussionmentioning
confidence: 99%
“…Auristatin PHE has fungicidal activity against C. neoformans and fungicidal or fungistatic activity against various species of Trichosporon (39,50). Auristatin PHE caused C. neoformans cells to arrest in a large-budded stage (50), suggesting that it might interfere with the microtubule dynamics in a manner similar to that of nocodazole in Saccharomyces cerevisiae (17).…”
mentioning
confidence: 99%
“…Broth microdilution assays (BMAs) with a large panel of fungi, with an emphasis on basidiomycetes, have shown that dolastatin 10 has selective antifungal activity against C. neoformans, and auristatin PHE has selective antifungal activity against C. neoformans and some species of Trichosporon (43,61). Other species in the genus Cryptococcus are not inhibited by high concentrations of these peptides.…”
mentioning
confidence: 99%
“…Furthermore, the susceptible organisms may share a unique target that enhances binding and/or interaction with the drug(s). Compared to dolastatin 10, auristatin PHE had lower MICs (43,61), exhibited concentration-dependent killing between the MIC and four times the MIC (43), and demonstrated increased activity as well as prolonged postantifungal effects in the presence of human serum (43,61). Iterative deconvolution in conjunction with an optimized C. neoformans microtubule immunolabeling procedure enabled us to investigate the mechanism of action of auristatin PHE (62).…”
mentioning
confidence: 99%